Indigenous utilization of medicinal plants in Kalasha tribes, District Chitral, Hindukush Range, Pakistan - Hadi, Fazal; Kılıc, Omer; Ullah, Saqib; Gul, Alia; Mujtaba Shah, Ghulam; Noreen, Shumaila; Bussmann, Rainer W (Ethnobotany Research and Applications, 2024)
Background: Indigenous people residing in the remote localities have practicing knowledge about the utilization of herbal resources to cure different ailments. Current study was conducted in Kalash valley District Chitral (Lower), Pakistan to investigate the indigenous medicinal plants, their local names, uses, etc. The valley inhabits peoples with unique culture and costumes and considered as the descendants of Alexander the great having their own way of plant utilization for medication. Methods: Data was collected by interviewing through questionnaires. During the fieldwork, 133 respondents (99 men and 34 women) of different age groups were selected and personal observations were also recorded. Data was analyzed by using parameters like Use Report (UR), Use Values (UV), Frequency of Citations (FC), Informant Consensus Factor (ICF) and Relative Frequency of Citations (RFC). The plants were provided with voucher numbers after collection and identification. Results: 90 medicinal plant species from 44 families and 75 genera used to treat 23 illnesses. Rosaceae was leading family with 13 species (14.45%) followed by Asteraceae with 07 species (7.80%) and Lamiaceae 06 (6.70%) species. The most frequently used plant component was fruit (34.44%) followed by leaves (26.66 %) and powder was found to be the primary method of preparations and are often either ingested or used topically. The maximum used value was reported for Allium cepa (0.92) and minimum (0.06) for Carum carvi. The digestive system disorders showed highest Informant Census Factor (ICF) values (0.71) followed by the Anti-microbial diseases having ICF value of 0.68, while the evil-eyes repellent plants showed least ICF (0.40) values. The highest RFC was recorded for Cannabis sativa (0.40) while Cedrus deodara has the lowest (0.10). Conclusion: The present findings revealed that the Kalash valley has diverse plant resources used for various human aliments. The current work will provide useful information for future studies on various aspects of botanical sciences from the area. Keywords: Medicinal uses, plant resources, Kalash Valley, Hindukush Range, Pakistan